Dysregulated CD25 and Cytokine Expression by γδ T Cells of Systemic Sclerosis Patients Stimulated With Cardiolipin and Zoledronate - Migalovich Sheikhet, Helena; Villacorta Hidalgo, Jose; Fisch, Paul; Balbir-Gurman, Alexandra; Braun-Moscovici, Yolanda; Bank, Ilan (Frontiers in Immunology, 2018)
Objectives:  T cells, a non-conventional innate lymphocyte subset containing cells that can be activated by lipids and phospho-antigens, are abnormally regulated in Systemic Sclerosis (SSc). To further evaluate the significance of this dysregulation, we compared how exposure to an auto-antigenic lipid, cardiolipin (CL), during co-stimulation with an amino-bisphosphonate (zoledronate, zol), affects the activation and cytokine production of SSc and healthy control (HC)  T cells. Methods: Expression of CD25 on V9+, V1+ and total CD3+ T cells in cultured peripheral blood mononuclear cells (PBMC), their binding of CD1d tetramers and the effect of monoclonal antibody (mAb) blockade of CD1d were monitored by flow cytometry after four days of in vitro culture. Intracellular production of IFN and IL-4 was assessed after overnight culture. Results: Percentages of (%) CD25+ among CD3+ and V+ T cells were elevated significantly in short-term cultured SSc PBMC (n=12) compared to HC (n=8). In SSc but not HC, CL and zol, respectively, suppressed %CD25+ V+ and V+ T cells but, when combined, CL+zol significantly activated both subsets in HC and partially reversed inhibition by the individual reagents in SSc. Importantly, V+ T cells in both SSc and HC were highly reactive with lipid presenting CD1d tetramers, and a CD1d blocking mAb decreased CL-induced enhancement of % SSc CD25+V+ T cells in the presence of zol. % IFN+ cells among V9+ T cells of SSc was lower than HC cultured in medium, CL, zol or CL+zol, whereas % IFN+ V1+ T cells was lower only in the presence of CL or CL+zol. %IL-4+ T cells were similar in SSc and HC in all conditions, with the exception of being increased in SSc V9+ T cells in the presence of CL. Conclusions: Abnormal functional responses of  T cell subsets to stimulation by CL and phospho-antigens in SSc may contribute to fibrosis and immune-suppression, characteristics of this disease.